-5x-10=-3+2x

Simple and best practice solution for -5x-10=-3+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x-10=-3+2x equation:


Simplifying
-5x + -10 = -3 + 2x

Reorder the terms:
-10 + -5x = -3 + 2x

Solving
-10 + -5x = -3 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-10 + -5x + -2x = -3 + 2x + -2x

Combine like terms: -5x + -2x = -7x
-10 + -7x = -3 + 2x + -2x

Combine like terms: 2x + -2x = 0
-10 + -7x = -3 + 0
-10 + -7x = -3

Add '10' to each side of the equation.
-10 + 10 + -7x = -3 + 10

Combine like terms: -10 + 10 = 0
0 + -7x = -3 + 10
-7x = -3 + 10

Combine like terms: -3 + 10 = 7
-7x = 7

Divide each side by '-7'.
x = -1

Simplifying
x = -1

See similar equations:

| 7(n-4)-(6-3n)=9n | | 0,001*0,001x=1/8 | | 2+3x=-5x-6 | | 2x-5=-2+x | | H=0.001x^2-X+27 | | 12h=72 | | (x+4)+(x+2)+(x+5)=2(x+1)+2(x+3) | | 90m^2+21mn-6n^2=0 | | T-75H=735 | | 9x+7-7x=4+x+5 | | -2=6+2x | | -20=b-5 | | 8-n=6+4n | | -9+7m=1+5m | | (m+2)(m-2)=0 | | 3(5-q)+6=9 | | 5(x+2)-(2x-7)= | | 10g=1100 | | x+4+x+2+x+5=2(x+1)+2(x+3) | | 10=1100 | | 3x-6=-14-7+6x+6 | | m^2-6m-33=-6 | | 5x-2=2x-35 | | 4x=38-2x+8 | | 5n^2-50n+105= | | Gsquared+3g=70 | | -10(-m)= | | b+3a=21 | | -4=6-z-z | | 2(3x+8)+9=7+4x | | 12x-4x^2=-7 | | 200=1.3x+0.04x^2 |

Equations solver categories